Real-time fuzzy position control and design of Star parallel robot - Aydin, Muhammet (Springer Heidelberg, 2024)
The goal of this study is to use fuzzy logic to develop and operate a specially made Star parallel robot inside a given working volume. The robot was constructed and outfitted with the required components after it was designed in SolidWorks with a working volume of 20 x 20 x 20 cm. Fuzzy logic was used in a MATLAB/Simulink real-time environment to accomplish real-time position control (RTPC). The objective was to use reference values of x = 100 mm, y = 200 mm, and z = 480 mm to regulate the end effector's location. The robot demonstrated the efficacy of the control mechanism by reaching the intended values in 8.286 s with a maximum error of 0.07%, as per the results. The investigation shed light on the trajectory of the robot as well as the error convergence over time. This paper presents a unique design with a working volume for a Star parallel robot, introducing the first application of real-time fuzzy logic control. Furthermore, the Star parallel robot's forward kinematic equations were published in the literature for the first time.
Keywords: Real-time control; Star parallel robot; Linear delta; Position control; Fuzzy control